The Importance of Religious Moderation and The Religiosity of The Karangwangi Village Community - Abdullah, Abdullah (Devotion : Journal of Research and Community Service, 2020)
Religious moderation is the key to creating tolerance and harmony, both at the local, national and global levels. This study aims to examine the importance of religious moderation and community religiosity in Karangwangi Village. The research method used is a qualitative method using a descriptive approach. Researchers will analyze the results of observations and interviews related to religious moderation and the level of religiosity in Karangwangi Village. Based on the results of the research, it is necessary to have an attitude of religious moderation and religiosity in religion as well as for differences of opinion and not to force one's will by means of violence. As well as needed religious figures and the role of the Karangwangi village community to create a moderate and religious attitude in all matters without any radical attitudes for the realization of harmony and peace